A reassessment of the cost-effectiveness of hormone replacement therapy in Sweden: Results based on the Women's Health Initiative randomised controlled trial - Niklas Zethraeus; Fredrik Borgström; Bengt Jönsson; John Kanis (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
The cost-effectiveness of hormone replacement therapy (HRT) based on a societal perspective is reassessed based on new medical evidence found in the Women's Health Initiative (WHI). Within a model framework using an individual state transition model the cost-effectiveness of 50-60 year old women with menopausal symptoms is assessed in Sweden. The Markov model has a 50 year time horizon divided into a cycle length of 1 year. The model consists of the following disease states: Coronary Heart Disease (CHD), Stroke, Venous thromboembolic events, breast cancer, colorectal cancer, hip fracture, vertebral fracture and wrist fracture. An intervention is modelled by its impact on the disease risks during and after the cessation of therapy. The model calculates costs and quality adjusted life years (QALYs) with and without intervention. The resulting cost per gained QALY is compared to the value of a gained QALY, which is set to SEK 600 000. The model requires data on clinical effects, risks, mortality rates, quality of life weights and costs valid for Sweden. The cost-effectiveness ratios are estimated at about SEK 10 000, which is far below the value of a gained QALY. Conditional on that HRT increases the quality of life weight more than 0.013 the therapy is cost-effective. In conclusion, given the new evidence in WHI, there is still a high probability that HRT is a cost-effective strategy for women with menopausal symptoms.
Keywords: D61; I10; I12; I19; 330; cost-effectiveness analysis; hormone replacement therapy; Markov model; Frauen; Pharmazeutisches Produkt; Kosten-Nutzen-Analyse; Markovscher Prozess; Schweden; Hormonpräparat